2012
DOI: 10.1634/theoncologist.2011-0450
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Hedgehog Signaling Pathway Inhibition for Cancer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 106 publications
1
28
0
1
Order By: Relevance
“…This phenomenon had been previously observed in various cancers 53. In cancers of the GI tract, SHH is often upregulated, thereby contributing to tumour formation and progression 44.…”
Section: The Hedgehog Dependence Receptors As Original Regulator Of Crcsupporting
confidence: 53%
“…This phenomenon had been previously observed in various cancers 53. In cancers of the GI tract, SHH is often upregulated, thereby contributing to tumour formation and progression 44.…”
Section: The Hedgehog Dependence Receptors As Original Regulator Of Crcsupporting
confidence: 53%
“…vismodegib, BMS-833293/XL139, IPI-926, LDE225, PF-04449913, LEQ 506, and TAK-441) either alone or in combination with chemotherapy for a variety of solid tumors (30). In 63 patients with locally advanced basal cell carcinoma, vismodegib led to a partial response in 22% of patients and a complete response in 21% of patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…They found that IL-23 signaling promotes tumor growth and progression, and the development of tumoral IL-17 response, resulting in an additional aggravation of disease progression (60). Efforts to target pathogenic Hedgehog signaling have steadily progressed from the laboratory to the clinic, and the recent approval of vismodegib for patients with advanced basal cell carcinoma represents an important milestone (61)(62)(63)(64)(65)(66). However, in a recent phase II study, vismodegib did not add to the efficacy of standard first-line treatment for metastatic colorectal cancer (67).…”
Section: Discussionmentioning
confidence: 99%